Capsaicin inhibits the stemness of anaplastic thyroid carcinoma cells by triggering autophagy‐lysosome mediated OCT4A degradation. (25th January 2022) - Wu, Liying; Xu, Shichen; Cheng, Xian; Zhang, Li; Wang, Yunping; Wu, Jing; Bao, Jiandong; Yu, Huixin; Lu, Rongrong
Abstract: Capsaicin (CAP) is a well‐known anti‐cancer agent. Recently, we reported capsaicin‐induced apoptosis in anaplastic thyroid cancer (ATC) cells. It is well accepted that the generation of cancer stem cells (CSCs) is responsible for the dedifferentiation of ATC, the most lethal subtype of thyroid cancer with highly dedifferentiation status. Whether CAP inhibited the ATC growth through targeting CSCs needed further investigation. In the present study, CAP was found to induce autophagy in ATC cells through TRPV1 activation and subsequent calcium influx. Meanwhile, CAP dose‐dependently decreased the sphere formation capacity of ATC cells. The stemness‐inhibitory effect of CAP was further by extreme limiting dilution analysis (ELDA). CAP significantly decreased the protein level of OCT4A in both 8505C and FRO cells. Furthermore, CAP‐induced OCT4A degradation was reversed by autophagy inhibitors 3‐MA and chloroquine, BAPTA‐AM and capsazepine, but not proteasome inhibitor MG132. Collectively, our study firstly showed CAP suppressed the stemness of ATC cells partially via calcium‐dependent autophagic degradation of OCT4A. Our study lent credence to the feasible application of capsaicin in limiting ATC stemness.